Effect of LiO Doping on the Surface and Catalytic Properties of the CrO/AlO System - G.A. El-Shobaky; A.M. Ghozza; H.G. El-Shobaky (Adsorption Science & Technology, 1998)
Two Cr 2 O 3 /Al 2 O 3 samples with the nominal compositions 0.06Cr 2 O 2 /Al 2 O 3 and 0.125Cr 2 O 3 /Al 2 O 3 (AlCr-I and AlCr-II, respectively) were prepared by mixing a known amount of finely powdered Al(OH) 3 with calculated amounts of CrO 3 , followed by drying at 120°C and calcination at 700°C and 800°C. Doped solid specimens were prepared by treating Al(OH) 3 samples with known amounts of LiNO 3 dissolved in the minimum amount of distilled water prior to mixing with CrO 3 . Dopant concentrations of 0.75, 1.50, 3.00 and 6.00 mol% Li 2 O were employed. The surface and catalytic properties of the pure and doped solids thus prepared were investigated using nitrogen adsorption at −196°C and studies of the catalysis of CO oxidation by O 2 over the solid specimens at 300–400°C. The results of such studies showed that Li 2 O doping followed by calcination at 700°C led to a maximum increase in the specific surface area, S BET , of 26% for AlCr-I and of 55% for AlCr-II when these samples were doped with 3.00 mol% Li 2 O. The reverse effect was found when the calcination temperature was increased to 800°C, where a decrease of 34% in the S BET value of the AlCr-II sample doped with 3.00 mol% Li 2 O was detected. The catalytic activities measured at 350°C over the pure and doped solids decreased on increasing the dopant concentration, the maximum decrease in such activity being ca. 33% and 50%, respectively, for the AlCr-I and AlCr-II samples calcined at 700°C. Doping led to noticable changes in the magnitude of the activation energy for the catalytic reaction. Such changes were accompanied by parallel changes in the value of the pre-exponential factor in the Arrhenius equation. These results may indicate that Li 2 O doping has no effect on the mechanism of the catalytic reaction but modifies (decreases) the concentration of catalytically active sites taking part in chemisorption during the catalysis of CO oxidation by O 2 .